2021
DOI: 10.1016/j.kint.2020.08.007
|View full text |Cite|
|
Sign up to set email alerts
|

HLA-D and PLA2R1 risk alleles associate with recurrent primary membranous nephropathy in kidney transplant recipients

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 30 publications
1
21
2
1
Order By: Relevance
“…35 Finally, HLA-A2 and HLA-DR12 may not be mechanistically involved in recurrent MN but represent haplotypes associated with recurrent MN via linkage disequilibrium. 36 HLA-DR12 is in linkage disequilibrium with HLA-DQA1*0501, which is not consistent with a study by Berchtold et al 10 that identified 2 donor noncoding HLA-D SNPs associated with recurrent MN, none of which were in linkage disequilibrium with MN risk alleles such as HLA-DQA1*0501. Although Berchtold et al 10 performed molecular HLA typing and validated their results in a replication cohort, their analysis did not include class I HLA loci.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…35 Finally, HLA-A2 and HLA-DR12 may not be mechanistically involved in recurrent MN but represent haplotypes associated with recurrent MN via linkage disequilibrium. 36 HLA-DR12 is in linkage disequilibrium with HLA-DQA1*0501, which is not consistent with a study by Berchtold et al 10 that identified 2 donor noncoding HLA-D SNPs associated with recurrent MN, none of which were in linkage disequilibrium with MN risk alleles such as HLA-DQA1*0501. Although Berchtold et al 10 performed molecular HLA typing and validated their results in a replication cohort, their analysis did not include class I HLA loci.…”
Section: Discussioncontrasting
confidence: 65%
“…Variables were chosen by supervised feature selection using penalized regression and ensemble tree machine learning techniques, which addressed the issues of overfitting and multiple testing associated with stepwise feature selection in our highdimensional dataset. 27,28 Although multiple studies have identified risk factors for recurrent MN after kidney transplantation such as detectable pretransplant anti-PLA2R autoantibody, steroid-free immunosuppression, and recipient HLA-A3 and donor risk HLA-D and PLA2R1 alleles, 3,6,9,10,29 prediction models to identify patients at high risk of recurrent MN (or other forms of glomerulonephritis) using routine pretransplant clinical data have not been comprehensively evaluated. These predictive approaches may inform clinicians on patients requiring closer monitoring of proteinuria, anti-PLA2R antibody titer, and/or protocol allograft biopsies to detect recurrent MN posttransplantation.…”
Section: Continued Next Pagementioning
confidence: 99%
“…Also, genetic factors have been associated to MN risk of recurrence. For example, the presence of SNP mutations on HLA-D and PLA2R loci confer more risk of recurrence when presented by the donor ( 67 ). Most recipients with recurrent MN are under CNI treatment, an effective therapy in native kidneys.…”
Section: The Harmsmentioning
confidence: 99%
“…Based on these, we suggested that the two genes might have a synergistic protective effect through PPARα regulation in the fatty acid metabolism pathway in IF/TA group, and the combined analysis of them might improve the diagnostic specificity. Moreover, FCGR2B, HLA-DQA2, and LTF are involved in tumor or organ transplantation [33][34][35]. It is reported that HLA-DQA2 is a HLA class II molecule expressed in the surface of antigen-presenting cells and involved in the recognition of peptide antigens by CD41 T cells [36].…”
Section: Discussionmentioning
confidence: 99%